Comunicando ciência: divulgação científica do Portal de Periódicos nos canais institucionais da UFSM - De Grandi, Maria Luiza Carvalho (2023)
This research is part of the context of science communication, having as its main theme the communication of science, delimited to institutional scientific dissemination within the Federal University of Santa Maria (UFSM). We have the scientific production of the scientific journals belonging to the Portal de Periódicos Eletrônicos of UFSM, and Using the qualitative methodology, combining case study and documentary research, the present study aims to answer the problem: how does the scientific dissemination of the journals of the Portal de Periódicos UFSM, in official institutional channels? The general objective of the research is to analyze how the scientific dissemination of periodicals belonging to the Portal de Periódicos takes place in the institutional channels of UFSM. As specific objectives, we sought to 1) Map UFSM's scientific journals to compose the research corpus; 2) Identify scientific dissemination strategies in UFSM's institutional channels; 3) Knowing the opinion of the editors of scientific journals about the obstacles of CD within UFSM; 4) Know the initiatives of the Dean of Graduate Studies and Research at UFSM for DC. To achieve the objectives, nine interviews were conducted with institution managers and editors of a sample of the Portal's journals.